2018
DOI: 10.1186/s12882-018-0906-5
|View full text |Cite
|
Sign up to set email alerts
|

COL4A5 and LAMA5 variants co-inherited in familial hematuria: digenic inheritance or genetic modifier effect?

Abstract: BackgroundAbout 40–50% of patients with familial microscopic hematuria (FMH) caused by thin basement membrane nephropathy (TBMN) inherit heterozygous mutations in collagen IV genes (COL4A3, COL4A4). On long follow-up, the full phenotypic spectrum of these patients varies a lot, ranging from isolated MH or MH plus low-grade proteinuria to chronic renal failure of variable degree, including end-stage renal disease (ESRD).MethodsHere, we performed Whole Exome Sequencing (WES) in patients of six families, presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
(31 reference statements)
1
29
0
Order By: Relevance
“…Mice with a double Lama5 knockout are fatal; however, mice with a hypomorphic Lama5 mutation (Lama5neo) that reduces laminin‐α5 expression, exhibit proteinuria, hematuria and cystic kidneys . It is probable, therefore, that although this might not represent true DI, the LAMA5 ‐p.Pro1243Leu variant behaves as a hypomorphic mutation that adds up to the Alport background…”
Section: True Non‐mendelian Digenic Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…Mice with a double Lama5 knockout are fatal; however, mice with a hypomorphic Lama5 mutation (Lama5neo) that reduces laminin‐α5 expression, exhibit proteinuria, hematuria and cystic kidneys . It is probable, therefore, that although this might not represent true DI, the LAMA5 ‐p.Pro1243Leu variant behaves as a hypomorphic mutation that adds up to the Alport background…”
Section: True Non‐mendelian Digenic Inheritancementioning
confidence: 99%
“…52 Several reports on renal genetic studies using NGS have identified rare patients with 2 mutations in separate genes but it is not clear whether they act as modifiers to each other or they represent true DI of nephrotic syndrome. 53 In our setup we studied a family where 54 It is probable, therefore, that although this might not represent true DI, the LAMA5-p.Pro1243Leu variant behaves as a hypomorphic mutation that adds up to the Alport background 55 Evidence for true DI was published while this review was in press, in a Libyan patient with distal renal tubular acidosis (dRTA).…”
Section: Selected Recent Publications On True Digenic Inheritancementioning
confidence: 99%
“…Arrows point to the mutations. Family 7 has one novel mutation, c. 3,782 G > A researches and cases reported that AS patients with COL4A5 mutations who have coinherited with COL4A3/COL4A4, MYO1E and LAMA5 mutations could exacerbated phenotypes (Lennon et al, 2015;Voskarides et al, 2018). These clinical symptoms occur mostly in the late disease stages and are thought to be secondary changes caused by primary GBM defects resulting from abnormalities in the collagen reticular structure (Braunisch et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…We looked for references in literature for the top suggested novel genes per disease by mantis-ml and have found supporting evidence for several genes. For instance, LAMA5 has been reported in the last two years to be co-inherited with COL4A5 in familial hematuria 21 and hosting variants that may affect pediatric nephrotic syndrome 22,23 . Moreover, NOS3 and NOS2-although not associated with CKD in OMIM -have already been implicated in Chronic Kidney Disease in a fair amount of studies 24, 25,26,27 , while MEF2C, a gene typically associated with mental disorders, has also been associated with estimated Glomerular Filtration Rate (eGFR) or proteinuria 28 .…”
Section: Application Of Mantis-ml Predictions To Triage Results From mentioning
confidence: 99%